'For ever England': The figurative colonization of Flanders. (March 2022) - Copeland, Todd
During the course of the First World War, the British presence in Belgium resulted in what one can describe as a figurative colonization of Flanders, an intensely defended region in which the British Empire suffered immense casualties. This process of figuratively recreating Flanders into British soil through the employment of possessive tropes took place in propaganda and literary works alike, with such terms as acquisitive equation and idealized interventions echoing those employed in the rhetoric of the British Empire during earlier eras in its imperial history.